2006
DOI: 10.1016/j.jaci.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Applying epidemiologic concepts of primary, secondary, and tertiary prevention to the elimination of racial disparities in asthma

Abstract: Despite medical and scientific advances, racial and ethnic disparities persist in US asthma morbidity and mortality rates. Progress in the elimination of these disparities will involve disentangling the contribution of social constructs, such as race, socioeconomic status, and culture, from that of the physical environment and genetic susceptibility. One approach to reducing asthma disparities is through the traditional disease prevention stages of intervention. As such, primary prevention targets reductions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 88 publications
3
54
0
1
Order By: Relevance
“…Despite progress in better recognition of asthma, however, concern remains that asthma is underdiagnosed and that children with undiagnosed disease remain at high risk of decreased quality of life and adverse outcomes. [42][43][44] Populations of concern include adolescents, 45 inner-city children, 42,43 and girls, who may present with more-subtle patterns of symptoms than boys. 46 However, 1 study in an urban area found rela- tively low prevalence of undiagnosed wheezing among children; the authors credited public awareness campaigns and asthma education for this finding.…”
Section: Asthma Is a Significant Public Health Burden About Which Manmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite progress in better recognition of asthma, however, concern remains that asthma is underdiagnosed and that children with undiagnosed disease remain at high risk of decreased quality of life and adverse outcomes. [42][43][44] Populations of concern include adolescents, 45 inner-city children, 42,43 and girls, who may present with more-subtle patterns of symptoms than boys. 46 However, 1 study in an urban area found rela- tively low prevalence of undiagnosed wheezing among children; the authors credited public awareness campaigns and asthma education for this finding.…”
Section: Asthma Is a Significant Public Health Burden About Which Manmentioning
confidence: 99%
“…Additional factors contributing to racial differences in adverse outcomes may include more-severe disease, variations in disease phenotypes and responsiveness to medication, environmental exposures, lag in uptake of medical advances to control asthma symptoms among health care providers who treat minority children, lack of cultural competence policies among health care providers, and lack of asthma education or difficulties in adopting certain asthma control methods for minority race/ethnic families. 44,71 Improving Outcomes for All Children With Asthma Is an Achievable Goal Removing the adverse impact of asthma in the life of a child is an achievable but demanding goal. Recognizing early symptoms, avoiding asthma triggers, arranging appropriate health care, and managing the schedule of medication administration can be complex for children and their families.…”
Section: Minority Children Have a Critical Need For Improved Intervenmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, asthma morbidity and mortality are disproportionately high and continue to increase among African Americans (49)(50)(51)(52). In 2002, African Americans had emergency department visit rates of 380%, hospitalization rates of 225%, and mortality rates of over 200% higher than non-Hispanic whites (CDC report, http://www.cdc.gov/nchs/products/pubs/pubd/ hestats/asthma/asthma.htm).…”
Section: African Americans and Disparities In Asthma And Allergic Dismentioning
confidence: 99%
“…In 2002, African Americans had emergency department visit rates of 380%, hospitalization rates of 225%, and mortality rates of over 200% higher than non-Hispanic whites (CDC report, http://www.cdc.gov/nchs/products/pubs/pubd/ hestats/asthma/asthma.htm). In addition, asthma appears to vary phenotypically according to ancestry, with African Americans showing different patterns of allergic sensitization, IgE levels, and bronchial hyperresponsiveness, when compared with Americans of European ancestry (52). These striking racial and ethnic disparities in disease characteristics and prevalence for common disorders such as allergic asthma cannot be explained entirely by environmental, social, cultural, or economic factors (53).…”
Section: African Americans and Disparities In Asthma And Allergic Dismentioning
confidence: 99%